Electrochemical device and electronic device

JP2025024028AActive Publication Date: 2025-02-19NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024195032
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-19
Estimated Expiration
2041-12-15

Smart Images

  • Figure 2025024028000001_ABST
    Figure 2025024028000001_ABST
Patent Text Reader

Abstract

To provide an electrochemical device and an electronic device that improve the rate characteristics of the electrochemical device under low and normal temperatures.SOLUTION: An electrochemical device includes a positive electrode piece, the positive electrode piece includes a positive electrode material layer, and the positive electrode material layer includes a positive electrode active material. In a scanning electron micrograph of a cross section of the positive electrode material layer, when the radius of the smallest circumscribing circle of the contour of positive electrode active material particles having an area of more than 5 μm2 is represented by Rc and the radius of the largest inscribing circle of the contour of the positive electrode active material particles having an area of more than 5 μm2 is represented by Ri, Rc and Ri satisfy 1<average value of Rc / Ri≤3. In the electrochemical device, when the positive electrode active material in the positive electrode material layer satisfies 1<average value of Rc / Ri≤3, the transport efficiency of lithium ions can be effectively improved, and the rate characteristics of the electrochemical device under room temperature and low temperature can be improved.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of electrochemistry, and in particular to electrochemical and electronic devices. [Background technology]

[0002] Due to the advantages of high energy density, long cycle life, and no memory effect, lithium ion batteries are widely used in fields such as wearable devices, smartphones, drones, electric vehicles, and large energy storage devices, and are currently the most promising new green chemical power source in the world. As lithium ion batteries are widely applied, the market requires further improvement of the overall performance of lithium ion batteries.

[0003] The positive electrode active material, negative electrode active material, and electrolyte in a lithium ion battery are important parameters that affect the performance of the lithium ion battery. Among them, the selection of the positive electrode active material affects the transport efficiency of lithium ions, and thus affects the electrochemical performance, such as the rate characteristics, of the electrochemical device. However, the conventional positive electrode active material needs to be further optimized to improve the rate characteristics of the electrochemical device. Summary of the Invention

[0004] An object of the present invention is to provide an electrochemical device and an electronic device that improve the rate characteristics of the electrochemical device at low and normal temperatures.

[0005] A first aspect of the present invention is an electrochemical device including a positive electrode piece, the positive electrode piece including a positive electrode material layer, the positive electrode material layer including a positive electrode active material, and a scanning electron microscope photograph of a cross section of the positive electrode material layer shows an area of ​​5 μm 2 The radius of the smallest circumscribing circle of the contour of the positive electrode active material particle is R c and the area is 5 μm 2 The radius of the maximum inscribed circle of the contour of the positive electrode active material particle is R i Then, R c and R i is 1 <Rc / R i The electrochemical device has an average value of R≦3. c / R i The average value of may be 1.1, 1.5, 1.8, 2, 2.3, 2.5, 2.8, 3, or may be in a range of any two of these values. Without being limited to any theory, it is believed that in the electrochemical device provided by the present invention, the positive electrode active material in the positive electrode material layer is 1 <R c / R i By satisfying the average value of R≦3, the transport efficiency of lithium ions during the charge and discharge process can be effectively improved, thereby improving the rate characteristics of the electrochemical device at room temperature and low temperature (for example, below 0° C.). c / R i It is presumed that the morphology of the positive electrode material layer in which the average value of is within the above range allows the positive electrode active material to maintain a stable crystal structure during cycles at a high rate, effectively improves the lithium ion absorption and release dynamics of the positive electrode active material, and provides good lithium ion transport properties, thereby improving the rate properties of the electrochemical device. In the present invention, the cross section of the positive electrode material layer refers to a cross section obtained by cutting the positive electrode material layer laterally along the thickness direction.

[0006] In some embodiments of the present invention, the area is 5 μm 2 The positive electrode active material particles include a first particle and a second particle, and the radius of the smallest circumscribing circle of the contour of the first particle is R c1 Let the radius of the maximum inscribed circle of the contour of the first particle be R i1 Then, R c1 and R i1 is 1 <R c1 / R i1 The average value of ≦1.5 is satisfied, and the radius of the smallest circumscribing circle of the outline of the second particle is R c2 Let the radius of the maximum inscribed circle of the contour of the second particle be R i2 Then, R c2 and R i2 is 1.5 <R c2 / R i2 The average value of is ≦3.

[0007] With respect to the cross-sectional area of ​​the positive electrode material layer, the area percentage of the first particles is more than 0% and 50% or less, and the area percentage B of the second particles is 30% to 80%. c1 / R i1 The average value of R may be 1.1, 1.2, 1.3, 1.4, 1.5, or may be in a range consisting of any two of these values. c2 / R i2 The average value of may be 1.6, 2, 2.5, 3, or may be in a range consisting of any two of these values. The area percentage of the first particles may be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or may be in a range consisting of any two of these values. The area percentage B of the second particles may be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or may be in a range consisting of any two of these values.

[0008] The first particles and the second particles are distributed in the positive electrode material layer in the above ratio, and after the compression process, the positive electrode material layer is filled with R c / R i By realizing the interlacing distribution between particles with different values, and improving the distribution network of the positive electrode active material and the conductive agent, the side reaction at the interface in the positive electrode material layer can be effectively reduced, and the transport efficiency of lithium ions and the electrical conductivity inside the positive electrode piece can be improved, thereby effectively improving the rate characteristics and cycle characteristics of the electrochemical device. If the area percentage B of the second particles is too small (e.g., less than 30%), the area percentage of the first particles is too large, and the compaction density of the positive electrode piece is reduced, affecting the transport efficiency of lithium ions. If the area percentage B of the second particles is too large (e.g., more than 80%), it will also lead to a reduction in the compaction density of the positive electrode piece, affecting the transport efficiency of lithium ions, and thereby affecting the rate characteristics of the electrochemical device at room temperature and low temperature. Adjusting the area percentage of the first particles and the area percentage of the second particles within the range of the present invention is advantageous to improving the rate characteristics of the electrochemical device at room temperature and low temperature. In the present invention, the compaction density of the positive electrode piece refers to the compaction density of the positive electrode material layer in the positive electrode piece.

[0009] In some embodiments of the present invention, the average cross-sectional area of ​​the first particles is smaller than the average cross-sectional area of ​​the second particles, which is advantageous for reducing lithium ion transport pathways and improving the rate capability of the electrochemical device.

[0010] In some embodiments of the present invention, the electrochemical device satisfies at least one of the conditions (a) to (b). (a) The positive electrode active material includes lithium manganate, and the lithium manganate includes doped lithium manganate and / or lithium manganate containing a coating layer. In the present invention, the doping element in the doped lithium manganate is not particularly limited as long as the object of the present invention can be realized, and for example, the doping element may include at least one of Al, Nb, Mg, Ti, F, B, Zr, W, Sr, Y, Ce, and La, but is not limited thereto. In the present invention, the element of the coating layer in the lithium manganate containing a coating layer is not particularly limited as long as the object of the present invention can be realized, and for example, the element of the coating layer may include at least one of Al, Sr, Zr, Ti, and B, but is not limited thereto. (b) The positive electrode active material includes a composite metal oxide of lithium and a transition metal element, the transition metal element including Mn and a metal element M1, the metal element M1 including at least one of Ni, Co, and Fe. With respect to the mass of the positive electrode active material, the mass fraction of Mn is 30% to 65%, and the mass fraction of the metal element M1 is 2% to 25%. When the electrochemical device satisfies at least one of the conditions (a) and (b), it is advantageous for improving the cycle characteristics and low-temperature rate characteristics of the electrochemical device.

[0011] In some embodiments of the present invention, the second particles include a metal element M2, and the metal element M2 includes at least one of Al, Mg, and Nb.

[0012] In some embodiments of the present invention, the mass fraction of the metal element M2 is 0.1% to 3% relative to the mass of the second particles. For example, the mass fraction of the metal element M2 may be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.5%, 3%, or a range consisting of any two of these values.

[0013] In the related art, manganese-containing positive electrode active materials (e.g., lithium manganate) are widely applied in electrochemical devices, such as lithium ion batteries. However, the Mn present in the lithium manganate 3+ Since manganese (Mn 2+ ) and migrates to the negative electrode through the electrolyte, destroying the solid electrolyte interface (SEI) film of the negative electrode, but active lithium is lost to repair the SEI film, thereby affecting the cycle characteristics and rate characteristics of the lithium ion battery. In the present invention, the negative electrode may refer to a piece of negative electrode.

[0014] The inventors of the present invention have found that, for an electrochemical device including a manganese-containing positive electrode active material, when the positive electrode active material includes a metal element M1, selecting the above metal element M1 is advantageous in improving the elution of manganese, thereby reducing damage to the negative electrode SEI film and loss of active lithium due to consumption of lithium for repairing the SEI film, thereby improving the cycle characteristics and rate characteristics of the electrochemical device.

[0015] The inventors of the present invention have found that when the second particles contain a metal element M2, by selecting the above metal element M2, the interfacial side reaction between the second particles and the electrolyte during the low-temperature charging and discharging process can be reduced, thereby improving the internal resistance of the positive electrode pieces and enhancing the low-temperature rate characteristics of the electrochemical device.

[0016] The inventors of the present invention found that if the mass fraction of the metal element M2 is too low (e.g., less than 0.1%), the improvement of the side reaction between the second particles and the electrolyte is not obvious. If the mass fraction of the metal element M2 is too high (e.g., more than 3%), the side reaction between the second particles and the electrolyte cannot be further improved, and the capacity per gram of the positive electrode active material is reduced. It was found that adjusting the mass fraction of the metal element M2 within the above range is advantageous for reducing the interfacial side reaction between the second particles and the electrolyte and improving the cycle characteristics of the electrochemical device. In the present invention, the negative electrode may refer to a negative electrode piece.

[0017] In some embodiments of the present invention, the volumetric particle size distribution of the positive electrode active material satisfies at least one of the following conditions: (c) 9 μm≦Dv50≦22 μm; and (d) 0.9≦(Dv90-Dv10) / Dv50≦2. For example, the Dv50 of the positive electrode active material may be 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, or 22 μm, or may be in a range of any two of these values. For example, the value of (Dv90-Dv10) / Dv50 may be 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2, or may be in a range of any two of these values. By adjusting the volumetric particle size distribution of the positive electrode active material to satisfy at least one of the conditions (c) to (d), it is advantageous to improve the rate characteristics of the electrochemical device at room temperature and low temperature. In the present invention, the Dv90 and Dv10 of the positive electrode active material are not particularly limited as long as the value of (Dv90-Dv10) / Dv50 is within the above range, and for example, the Dv90 of the positive electrode active material is 15 μm to 40 μm, and the Dv10 of the positive electrode active material is 0.5 μm to 6 μm. Here, the value of (Dv90-Dv10) / Dv50 mainly reflects the particle size distribution of the positive electrode active material.

[0018] In some embodiments of the present invention, the electrochemical device further includes an electrolyte, the electrolyte including a chain carbonate ester and a cyclic carbonate ester, and when the mass fraction of the chain carbonate ester is ω1 and the mass fraction of the cyclic carbonate ester is ω2 relative to the mass of the electrolyte, ω2 is 25% to 50%, and ω1 / ω2 is 0.75 to 2.5. For example, the mass fraction of the cyclic carbonate ester ω2 may be 25%, 30%, 35%, 40%, 45%, 50%, or may be in a range of any two of these values. The value of ω1 / ω2 may be 0.75, 1, 1.25, 1.5, 1.75, 2, 2.25, 2.5, or may be in a range of any two of these values.

[0019] Without being limited to any theory, c / R i In addition to adjusting the average value, the inclusion of a chain carbonate ester and a cyclic carbonate ester in the electrolyte creates a synergistic effect between the positive electrode active material and the electrolyte, improving the lithium ion transport path, particularly the lithium ion transport efficiency at the interface between the positive electrode active material and the electrolyte, thereby improving the rate characteristics of the electrochemical device.

[0020] Without being limited to any theory, if the mass fraction ω2 of the cyclic carbonate is too low (e.g., less than 25%), a good synergistic effect for improving the transport efficiency of lithium ions cannot be formed between the cyclic carbonate and the chain carbonate, and if the mass fraction ω2 of the cyclic carbonate is too high (e.g., more than 50%), the viscosity of the electrolyte increases, which is unfavorable to the transport of lithium ions, thereby affecting the rate characteristics of the electrochemical device. If the value of ω1 / ω2 is less than 0.75 or more than 2.5, both will affect the synergistic effect between the cyclic carbonate and the chain carbonate, thereby affecting the transport efficiency of lithium ions. By adjusting the values ​​of the mass fraction ω2 and ω1 / ω2 of the cyclic carbonate within the range of the present invention, the positive electrode active material can be sufficiently infiltrated, thereby improving the transport efficiency of lithium ions at the interface between the positive electrode active material and the electrolyte, and further improving the rate characteristics of the electrochemical device.

[0021] In some embodiments of the present invention, ω1 satisfies 35%≦ω1≦65%. For example, the mass fraction ω1 of the chain carbonate ester may be 35%, 40%, 45%, 50%, 55%, 60%, 65%, or may be in a range consisting of any two of these values. Without being limited by any theory, adjusting the mass fraction ω1 of the chain carbonate ester within the range of the present invention is favorable for forming a good synergistic effect between the cyclic carbonate ester and the chain carbonate ester, improving the transport efficiency of lithium ions, and thereby improving the rate characteristics of the electrochemical device.

[0022] In some embodiments of the present invention, the chain carbonate ester includes at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethyl propyl carbonate (EPC), dipropyl carbonate (DPC), methyl isopropyl carbonate, methyl butyl carbonate, and dibutyl carbonate (DBC). Without being limited to any theory, the selection of the chain carbonate ester is advantageous for improving the transport efficiency of lithium ions and the rate characteristics of the electrochemical device.

[0023] In some embodiments of the present invention, the cyclic carbonate ester includes at least one of ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). Without being limited to any theory, the selection of the above cyclic carbonate ester is advantageous for improving the transport efficiency of lithium ions and the rate characteristics of the electrochemical device.

[0024] In some embodiments of the present invention, the electrolyte contains a sulfonate compound, and when the mass fraction of the sulfonate compound relative to the mass of the electrolyte is A, A satisfies 0.006≦A / B≦0.1. For example, the value of A / B may be 0.006, 0.008, 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, or may be in a range consisting of any two of these values. Without being limited by any theory, the sulfur-oxygen double bond in the sulfonate compound is favorable for improving the stability of the SEI film and reducing the deposition of eluted manganese on the negative electrode, thereby improving the cycle characteristics of the electrochemical device. At the same time, when the value of A / B is within the range of the present invention, it is favorable for a synergistic effect to occur between the sulfonate compound and the positive electrode active material, which improves the stability of the SEI film and improves the transport efficiency of lithium ions, and further improves the rate characteristics of the electrochemical device.

[0025] In some embodiments of the present invention, A satisfies 0.5%≦A≦10%. For example, the mass fraction A of the sulfonate ester compound may be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or may be in a range consisting of any two of these values. Without being limited by any theory, when the mass fraction A of the sulfonate ester compound is too low (e.g., less than 0.5%), the improvement on the stability of the SEI film is not obvious, and when the mass fraction A of the sulfonate ester compound is too high (e.g., more than 10%), a too thick or too dense SEI film is formed, which inhibits the transport of lithium ions and leads to a decrease in the rate performance of the electrochemical device.

[0026] Preferably, the sulfonate compound includes at least one of the compounds I-1 to I-14 having the following structures: Selecting a sulfonate compound having the following structure is advantageous for improving the stability of the SEI film and reducing the deposition of eluted manganese on the negative electrode, thereby improving the cycle characteristics of the electrochemical device. [ka]

[0027] In some embodiments of the present invention, the electrochemical device further includes a negative electrode sheet, the negative electrode sheet includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of artificial graphite, natural graphite, and hard carbon. Without being limited by any theory, by selecting the above negative electrode active material, it is advantageous to form a synergistic effect between the positive electrode active material and / or the electrolyte, and improve the cycle characteristics and rate characteristics of the electrochemical device.

[0028] In the present invention, the positive electrode active material may include, but is not limited to, a composite oxide, and at least one of a sulfide, a selenide, and a halide of the composite oxide. The composite oxide may include, but is not limited to, LiMn2O4, Li(Ni a1 Co b1 Mn c1 )O2(0 < a1 < 1, 0 < b1 < 1, 0 < c1 < 1, a1 + b1 + c1 = 1), LiNi 1-y1 Co y1 O2(0 < y1 < 1), LiNi 2-y3 Mn y3 O4(0 < y3 < 2), Li(Ni a3 Co b3 Al c3 )O2(0 < a3 < 1, 0 < b3 < 1, 0 < c3 < 1, a3 + b3 + c3 = 1), and LiMn p Fe q PO4(0 < p < 1, 0 < q < 1, p + q = 1), and at least one of LiFePO4, but is not limited thereto.

[0029] Optionally, an amorphous compound or a crystalline compound may be present on the surface of the composite oxide, and the amorphous or crystalline compound may include, but is not limited to, at least one of an oxide of element Z, a hydroxide of element Z, an oxyhydroxide of element Z, an oxycarbonate of element Z, and a basic carbonate of element Z. Here, element Z may include, but is not limited to, at least one of Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, and Zr.

[0030] In the present invention, the method for preparing the composite oxide containing an amorphous compound or a crystalline compound on the surface is not particularly limited as long as the object of the present invention can be realized, and examples thereof include a spray method and a deep method.

[0031] In the present invention, the positive electrode material layer may further include a conductive agent. In the present invention, the conductive agent is not particularly limited as long as the object of the present invention can be realized. For example, the conductive agent may include at least one of conductive carbon black (SuperP), carbon nanotubes (CNTs), carbon fibers, Ketjen black, graphene, metal materials, and conductive polymers, but is not limited thereto. The carbon nanotubes may include single-walled carbon nanotubes and multi-walled carbon nanotubes, but is not limited thereto. The carbon fibers may include, but are not limited to, vapor grown carbon fibers (VGCF) and / or nano carbon fibers. The metal materials may include, but are not limited to, metal powders and metal fibers, and specifically, the metals may include, but are not limited to, at least one of copper, nickel, aluminum, and platinum. The conductive polymers may include, but are not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene, and polypyrrole. In the present invention, the mass fraction of the conductive agent is 0.5% to 5% with respect to the mass of the positive electrode material layer.

[0032] In the present invention, the positive electrode material layer may include a positive electrode binder. In the present invention, the positive electrode binder is not particularly limited as long as the object of the present invention can be realized, and includes, for example, at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethyleneoxy, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic acid (ester)-modified styrene butadiene rubber, epoxy resin, and nylon, but is not limited thereto.

[0033] In the present invention, the positive electrode piece includes a positive electrode current collector. Here, the positive electrode current collector is not particularly limited as long as the object of the present invention can be realized, and may include, for example, aluminum foil, aluminum alloy foil, and composite current collector, but is not limited thereto. In the present invention, the thickness of the positive electrode current collector is not particularly limited as long as the object of the present invention can be realized, and for example, the thickness is 8 μm to 20 μm.

[0034] Optionally, the positive electrode piece may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. In the present invention, the composition of the conductive layer is not particularly limited, and may be a conductive layer common in the art, for example, including, but not limited to, the conductive agent and the positive electrode binder described above.

[0035] In the present invention, the negative electrode material layer may contain a conductive agent. In the present invention, the conductive agent is not particularly limited as long as the object of the present invention can be realized, and may contain, for example, at least one of the conductive agents described above, but is not limited thereto.

[0036] In the present invention, the negative electrode material layer may further include a negative electrode binder. In the present invention, the negative electrode binder is not particularly limited as long as the object of the present invention can be realized, and may include, for example, at least one of difluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethyleneoxy, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber, acrylic acid (ester)-modified styrene-butadiene rubber, an epoxy resin, and nylon, but is not limited thereto.

[0037] In the present invention, the negative electrode piece includes a negative electrode current collector. Here, the negative electrode current collector is not particularly limited as long as the object of the present invention can be realized, and may include, for example, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, and composite current collector, but is not limited thereto. In the present invention, the thickness of the negative electrode current collector is not particularly limited as long as the object of the present invention can be realized, and for example, the thickness is 4 μm to 12 μm.

[0038] Optionally, the negative electrode piece may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. In the present invention, the composition of the conductive layer is not particularly limited, and may be a conductive layer common in the art, and may include, but is not limited to, the above-mentioned conductive agent and the above-mentioned negative electrode binder.

[0039] In the present invention, the electrolyte may further include a non-aqueous solvent. In the present invention, the non-aqueous solvent is not particularly limited as long as the object of the present invention can be realized, and may include at least one of, for example, a carboxylic acid ester compound, an ether compound, and other organic solvents, but is not limited thereto. The above-mentioned carboxylic acid ester compounds include methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, γ-butyrolactone, 2,2-difluoroethyl acetate, valerolactone, butyrolactone, 2-fluoroethyl acetate, 2,2-difluoroethyl acetate, ethyl trifluoroethyl acetate, 2,2,3,3,3-pentafluoropropionate, 2,2 ,3,3,4,4,4,4-heptafluorobutyrate methyl, 4,4,4-trifluoro-3-(trifluoromethyl)butyrate methyl, 2,2,3,3,4,4,5,5,5,5-nonafluorovalerate ethyl, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9,9-heptadecafluorononanoate methyl, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9,9-heptadecafluorononanoate ethyl may include at least one of, but is not limited to, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dibutyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, and bis(2,2,2-trifluoroethyl)ether. The other organic solvents may include, but are not limited to, at least one of ethyl vinyl sulfone, methyl isopropyl sulfone, isopropyl sec-butyl sulfone, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters.

[0040] In the present invention, the electrolyte may further contain a lithium salt. In the present invention, the lithium salt is not particularly limited as long as the object of the present invention can be realized, and examples of the lithium salt include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalate)borate (LiB(C2O4)2), lithium difluorooxalateborate (LiBF2(C2O4)), lithium hexafluoroantimonate (LiSbF6), lithium perfluorobutylsulfonate (LiC4F9SO3), lithium perchlorate (LiClO4), lithium aluminate (LiAlO2), lithium tetrachloroaluminate (LiAlCl4), lithium bissulfonimide (LiN(C x F 2x+1 SO2)(C y F 2y+1 The lithium salt may include at least one of SO2, where x and y are each a natural number of 4 or less), lithium chloride (LiCl), and lithium fluoride (LiF), but is not limited thereto. Preferably, the lithium salt includes LiPF6. In the present invention, the concentration of the lithium salt is not particularly limited as long as the object of the present invention can be realized, and the concentration is, for example, 0.5 mol / L to 3 mol / L, preferably 0.5 mol / L to 2 mol / L, and more preferably 0.6 mol / L to 1.5 mol / L.

[0041] The electrochemical device of the present invention further includes a separator, and in the present invention, the separator is not particularly limited as long as the object of the present invention can be realized, and may include, for example, at least one of polyethylene (PE), polypropylene (PP), polytetrafluoroethylene-based polyolefin (PO) separators, polyester films (e.g., polyethylene terephthalate (PET) films), cellulose films, polyimide films (PI), polyamide films (PA), spandex and aramid films, woven films, nonwoven films (nonwoven fabrics), microporous films, composite films, separators, press films, and spun films, but is not limited thereto. The separator of the present invention may have a porous structure, and the size of the pores is not particularly limited as long as the object of the present invention can be realized, and for example, the size of the pores may be 0.01 μm to 1 μm. In the present invention, the thickness of the separator is not particularly limited as long as the object of the present invention can be realized, and for example, the thickness may be 5 μm to 500 μm.

[0042] For example, the separator may include a separator substrate layer and a surface treatment layer. The separator substrate layer may be a nonwoven fabric, a membrane, or a composite membrane having a porous structure, and the material of the separator substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide, but is not limited thereto. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be used. Optionally, a surface treatment layer is provided on at least one surface of the separator substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer formed by mixing a polymer and an inorganic material.

[0043] The polymer layer includes a polymer, and the polymer material may include, but is not limited to, at least one of vinylidene fluoride, vinylidene fluoride-hexafluoropropyl copolymer, polyacrylonitrile, polyimide, acrylonitrile-butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, polymethyl methacrylate, polymethyl acrylate, polyethyl acrylate, acrylic acid-styrene copolymer, polydimethylsiloxane, sodium polyacrylate, and carboxymethyl cellulose. The inorganic layer may include, but is not limited to, inorganic particles and inorganic binders, and in the present invention, the inorganic particles are not particularly limited and may include, for example, at least one of ceramic, aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. In the present invention, the inorganic layer binder is not particularly limited, and may include, for example, at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene, but is not limited thereto.

[0044] The electrochemical device of the present invention is not particularly limited and may include any device in which an electrochemical reaction occurs. In some embodiments, the electrochemical device may include, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, and a lithium ion polymer secondary battery.

[0045] The preparation process of the electrochemical device is well known to those skilled in the art, and the present invention is not particularly limited, for example, including but not limited to the following steps: Positive electrode pieces, separators, and negative electrode pieces are stacked in order, and if necessary, the stacked electrode pieces are wound, folded, etc. to obtain a wound electrode group, and the electrode group is placed in a packaging bag, and the electrolyte is poured into the packaging bag, and the bag is sealed to obtain an electrochemical device. Alternatively, positive electrode pieces, separators, and negative electrode pieces are stacked in order, and the four corners of the entire stacked structure are fixed with tape to obtain a stacked electrode group, and the electrode group is placed in a packaging bag, and the electrolyte is poured into the packaging bag, and the bag is sealed to obtain an electrochemical device. In addition, in order to prevent the internal pressure rise and overcharging and discharging of the electrochemical device, an overcurrent protection element, a lead plate, etc. may be provided in the packaging bag as necessary.

[0046] A second aspect of the present invention provides an electronic device comprising an electrochemical device according to any of the embodiments of the present invention. The electrochemical device provided by the present invention has good rate and cycle characteristics, and therefore the electronic device provided by the present invention has a long service life.

[0047] The electrochemical device of the present invention is not particularly limited and may be used in any electronic device known in the prior art. In some embodiments, the electronic device of the present invention may include, but is not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copy machines, portable printers, stereo headsets, video recorders, LCD televisions, portable cleaners, portable CD players, mini discs, transceivers, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, bicycle auxiliaries, bicycles, lighting equipment, toys, game consoles, watches, power tools, flashlights, cameras, large household storage batteries, and lithium ion capacitors.

[0048] The present invention relates to an electrochemical device including a positive electrode piece, the positive electrode piece including a positive electrode layer, the positive electrode layer including a positive electrode active material, and a scanning electron micrograph of a cross section of the positive electrode layer showing a cross-sectional area of ​​5 μm 2 The radius of the smallest circumscribing circle of the contour of the positive electrode active material particle is R c The cross-sectional area is 5 μm 2 Let R be the radius of the maximum inscribed circle of the particle contour. i Then, R c and R i is 1 <R c / R i The present invention provides an electrochemical device in which the positive electrode active material in the positive electrode material layer satisfies the average value of ≦3. <R c / R i By satisfying the average value≦3, the transport efficiency of lithium ions in the positive electrode pieces can be effectively improved, thereby improving the rate characteristics of the electrochemical device at normal and low temperatures. [Brief description of the drawings]

[0049] In order to more clearly describe the embodiments of the present invention and the technical solutions of the prior art, the following briefly describes the drawings used in the embodiments and the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention. [Figure 1] FIG. 1 is a scanning electron microscope photograph of a cross section of a positive electrode material layer in one embodiment of the present invention. [Diagram 2] 2 is a schematic cross-sectional view of a positive electrode piece according to one embodiment of the present invention, in which: 10, positive electrode current collector; 20, positive electrode material layer; 21, positive electrode active material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0050] In order to make clear the objectives, technical solutions and advantages of the present invention, the present invention will be described in detail below with reference to the drawings and examples. Obviously, the described examples are only some of the embodiments of the present invention, and not all of the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention belong to the protection scope of the present invention.

[0051] 1 shows a scanning electron microscope photograph of a cross section of a positive electrode material layer in one embodiment of the present invention, and as can be seen from the drawing, there are differences in size and shape of particles of the positive electrode active material 21. The minimum circumscribing circle of the outline of particle C is R1, the maximum inscribing circle of the outline of particle C is R2, the minimum circumscribing circle of the outline of particle D is R3, and the maximum inscribing circle of the outline of particle D is R4. Here, particle C is an example of the first particle in the present invention, and particle D is an example of the second particle in the present invention.

[0052] FIG. 2 is a schematic cross-sectional view of a positive electrode piece in one embodiment of the present invention, in which a positive electrode material layer 20 is present on both surfaces of a positive electrode current collector 10, the direction indicated by the arrow in the figure is the thickness direction of the positive electrode material layer 20, and the cross section of the positive electrode material layer described in the present invention refers to one obtained by crossing along the direction of the arrow in the figure.

[0053] In the embodiment of the present invention, the R c1 / R i1 and the average value of the second particle R c2 / R i2 The average value of can be controlled by controlling the ratio of the radius of the minimum circumscribing circle to the radius of the maximum inscribing circle of the outline of the raw material particles, and the Dv50 of the raw material, and by comprehensively adjusting conditions such as the stirring speed or the firing temperature during the preparation process of the positive electrode active material.

[0054] In the embodiments of the present invention, the present invention will be described using a lithium ion battery as an example of an electrochemical device, but the electrochemical device of the present invention is not limited to a lithium ion battery.

[0055] Working Example Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples and comparative examples. Various tests and evaluations are performed as described below. In addition, "parts" and "%" are based on mass unless otherwise specified.

[0056] Measurement methods and devices: R i and Rc Measurement: Under the condition of 25°C, the lithium-ion battery was charged to 4.2V at a constant current of 0.5C, further charged at a constant voltage of 0.05C under the condition of 4.2V, and discharged to 2.8V at a constant current of 1C. The lithium-ion battery was disassembled, the positive electrode pieces were washed with DMC, and dried at 60°C for 2h. After that, the positive electrode pieces were cut along the thickness direction of the positive electrode pieces themselves using an ion polishing machine, and a flat positive electrode piece cross section was obtained. The cross section was measured using a scanning electron microscope (SEM), and an SEM image with a magnification of 1000 times was selected.

[0057] The software ImageJ was used to perform feature recognition on the above SEM images, and the cross section was determined to be completely within the image field and with a cross-sectional area of ​​5 μm 2 Randomly select 100 particles, and use an algorithm to calculate the radius R of the maximum inscribed circle of the particle. i and the radius of the minimum circumscribed circle R c were calculated respectively (see "Kenneth C. Williams, Wei Chen, Sebastian Weeger, Timothy J. Donohue, Particle shape characterisation and its application to discrete element modelling, Particuology, Volume 12, 2014, Pages 80-89, ISSN 1674-2001").

[0058] R c1 , R i1 , R c2 , R i2 The measurement method is R i and R c It was the same as:

[0059] R c3 and R i3 The measurement of R was carried out by first preparing manganese dioxide into a slurry, coating it on a substrate to form a film layer, and then i and R cThe solid content of the slurry (e.g., 75 wt%) and the type of the substrate are not particularly limited as long as the object of the present invention can be achieved. c4 and R i4 , R c5 and R i5 The measurement of R c3 and R i3 The measurement method was referred to.

[0060] Measurement of the area of ​​the primary and secondary particles and calculation of the area percentage: Calculate the area of ​​the particles using the software ImageJ and recognize the R c / R i The ratio was used to determine whether the particle belonged to the first particle or the second particle, and the sum of the particles with different attributes was taken as the area of ​​the first particle or the second particle, with the area percentage of the first particle being the area of ​​the first particle / area of ​​the image × 100%, and the area percentage of the second particle being the area of ​​the second particle / area of ​​the image × 100%.

[0061] Measurement of particle size of positive electrode active material: The particle size of the positive electrode active material was measured using a Malvern particle sizer, and the positive electrode active material was dispersed in ethanol and ultrasonicated for 30 minutes, after which it was added to the Malvern particle sizer and measurement was started. In the volume-based particle size distribution of the positive electrode active material, from the small particle size side, the particle size at which the cumulative volume was 10% was Dv10 of the positive electrode active material, the particle size at which the cumulative volume was 50% was Dv50 of the positive electrode active material, and the particle size at which the cumulative volume was 90% was Dv90 of the positive electrode active material.

[0062] Determination of elemental content: In the SEM image of the cross section of the positive electrode piece obtained above, the second particles were identified based on the particle size and area of ​​the particles in the image, and the doping elements and element contents were determined by measuring with an energy dispersive spectroscopy (EDS).

[0063] The positive electrode material layer of the positive electrode piece washed with DMC was removed with a blade, and dissolved in a mixed solvent (for example, a mixed solvent of 10 ml of aqua regia (a mixture of nitric acid and hydrochloric acid in a volume ratio of 1:1) and 2 ml of HF was used for 0.4 g of positive electrode active material), diluted to 100 mL, and the element contents in the solution were measured with an inductively coupled plasma (ICP) analyzer.

[0064] Measurement of the pressed density of the cathode strips: Under the condition of 25 ° C, the lithium ion battery was charged to 4.2 V at a constant current of 0.5 C, further charged at a constant voltage of 0.05 C under the condition of 4.2 V, and discharged to 2.8 V at a constant current of 1 C. The lithium ion battery was disassembled, the positive electrode pieces were washed with DMC, and dried at 60 ° C for 2 h, after which five positive electrode pieces of 5 cm x 5 cm in size were cut and the thickness of each positive electrode piece was measured with a micrometer of one ten-thousandth, and was set as d0 cm. The positive electrode material layer of the positive electrode piece was removed with a blade, the mass of the positive electrode material layer was measured with a tenpei and was set as mg, and the thickness of the positive electrode current collector from which the positive electrode material layer was removed with a micrometer of one ten-thousandth was set as d cm, and the compressed density of the positive electrode material layer was calculated by the following formula. Compressed density P = m / [25 × (d0-d)], unit g / cm 3 .

[0065] The compressed density of the positive electrode material layer is the average value of the compressed densities of the positive electrode material layers of the five positive electrode pieces obtained by the above cutting.

[0066] Measurement of particle size in the positive electrode layer: Under the condition of 25°C, the lithium ion battery was charged to 4.2V at a constant current of 0.5C, further charged at a constant voltage of 4.2V at 0.05C, and then discharged to 2.8V at a constant current of 1C. The lithium ion battery was disassembled, and the disassembled positive electrode pieces or negative electrode pieces were baked into powder at 400°C in a vacuum. The particle size was then measured using a particle size analyzer, and the values ​​of Dv10, Dv50, and Dv90 were obtained.

[0067] Here, Dv90 refers to the particle size at which the cumulative volume is 90% from the smaller particle size side in the volume-based particle size distribution, Dv50 refers to the particle size at which the cumulative volume is 50% from the smaller particle size side in the volume-based particle size distribution, and Dv10 refers to the particle size at which the cumulative volume is 10% from the smaller particle size side in the volume-based particle size distribution.

[0068] Measurement of rate characteristics and 25℃ cycle characteristics: (1) 25℃ 2C room temperature rate characteristics and 25℃ cycle characteristics Under the condition of 25°C, the lithium-ion battery is charged to 4.2V at a constant current of 0.5C, and then charged at a constant voltage of 0.05C at 4.2V, and then discharged to 2.8V at a constant current of 0.2C. The discharge capacity is D 01 The lithium-ion battery was charged to 4.2 V at a constant current of 0.5 C, further charged to 0.05 C at a constant voltage under the condition of 4.2 V, and discharged to 2.8 V at a constant current of 2 C, and the discharge capacity was recorded as D1. 25°C 2C rate retention rate (%) = D1 / D 01 ×100%.

[0069] According to the above operation steps, the lithium-ion battery is cycled with "0.5C charge-2C discharge" several times, cycled 1000 times, and the discharge capacity after the 1000th cycle is D 10 The capacity retention rate after 1000 cycles at 25°C (%) = D 10 / D 01 ×100%.

[0070] (2) -10℃ 1C low temperature rate characteristics Under the condition of 25°C, the lithium-ion battery is charged to 4.2V at a constant current of 0.5C, and then charged at a constant voltage of 0.05C at 4.2V, and then discharged to 2.8V at a constant current of 1C. The discharge capacity is D 02The lithium-ion battery was charged to 4.2 V at a constant current of 0.5 C under the condition of 25°C, and further charged at a constant voltage of 0.05 C under the condition of 4.2 V, and the temperature was adjusted to -10°C, and the cell was left for 30 min, and then discharged to 2.8 V at a constant current of 1 C, and the discharge capacity was recorded as D2. -10°C 1C rate retention rate (%) = D2 / D 02 ×100%.

[0071] Measurement of cycle characteristics: Capacity retention rate at 40℃ for 500 cycles: The lithium-ion battery was charged at 40°C with a constant current of 0.5C to 4.2V, then charged at a constant voltage until the current became 0.05C, left for 5min, and discharged at a constant current of 1C to 2.8V, which constituted one charge-discharge cycle. The discharge capacity was D 03 According to the above operation steps, the lithium ion battery was cycled 500 times, and the discharge capacity after the 500th cycle was measured as D3. Capacity retention rate after 500 cycles at 40°C (%) = D3 / D 03 ×100%.

[0072] Determination of manganese content in anode pieces: After 500 cycles at 40℃, the lithium-ion battery was disassembled after full discharge, the negative electrode pieces were taken out, washed with DMC, and dried at 60℃ for 2h. The negative electrode material layer of the negative electrode pieces was then removed with a blade, dissolved in a mixed solvent (e.g., 0.4g of negative electrode active material in 10ml of aqua regia (a mixture of nitric acid and hydrochloric acid in a volume ratio of 1:1)), diluted to 100ml, and the manganese content in the solution was measured by an ICP analyzer.

[0073] Example 1-1 <Preparation of positive electrode piece> 203.3 kg of lithium carbonate (wherein the mass fraction of lithium element is 18.71%), R c3 / R i31000 kg of manganese dioxide (wherein the mass fraction of Mn element is 60.22%) having an average value of 2.9 and Dv50 of 17.2 μm, and 56.2 kg of aluminum oxide (Al2O3, the mass fraction of aluminum element is 52.91%), which is a compound containing M2 metal element, were weighed out and mixed in a high-speed mixer at a rotation speed of 300 r / min for 20 minutes to obtain a mixture, which was placed in an air kiln, heated to 790°C at a rate of 5°C / min, maintained for 24 hours, naturally cooled, taken out, and sieved through a 300 mesh sieve to obtain a manganese-containing composite metal oxide, i.e., LMO. c3 is the radius of the smallest circumscribing circle of the manganese dioxide particle, and R i3 is the radius of the maximum inscribed circle of the outline of the manganese dioxide particle.

[0074] The positive electrode active material LMO, the conductive agent SuperP, and the binder polyvinylidene fluoride were mixed in a mass ratio of 96:2.4:1.6, N-methylpyrrolidone (NMP) was added, and the mixture was stirred with a vacuum stirrer until it became uniform, to obtain a positive electrode slurry, in which the solid content of the positive electrode slurry was 75 wt%. The positive electrode slurry was uniformly coated on one surface of an aluminum foil serving as a positive electrode current collector with a thickness of 10 μm, and the aluminum foil was dried at 85 ° C. to obtain a positive electrode piece with a positive electrode material layer coated on one side and a coating layer thickness of 110 μm. The above steps were repeated on the other surface of the aluminum foil to obtain a positive electrode piece with a positive electrode material layer coated on both sides. Then, after cold rolling, cutting, and slitting, the mixture was dried under vacuum conditions at 85 ° C. for 4 h, and a positive electrode piece with a size of 74 mm × 867 mm was obtained. Here, the R of the positive electrode active material was c / R i The average value of was 2.9, and Dv50 was 17.9 μm.

[0075] <Preparation of negative electrode piece> The negative electrode active material artificial graphite, the conductive agent SuperP, the thickener sodium carboxymethylcellulose (CMC), and the binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 96.4:1.5:0.5:1.6, deionized water was added, and the negative electrode slurry was obtained by a vacuum mixer, where the solid content of the negative electrode slurry was 70 wt%. The negative electrode slurry was uniformly coated on one surface of the copper foil, which was a negative electrode current collector with a thickness of 10 μm, and the copper foil was dried at 85 ° C., and a negative electrode piece with a negative electrode material layer coated on one side with a coating layer thickness of 130 μm was obtained. The above steps were repeated on the other surface of the copper foil, and a negative electrode piece with a negative electrode material layer coated on both sides was obtained. Then, after cold rolling, cutting, and slitting, it was dried under vacuum conditions at 120 ° C for 12 h, and a negative electrode piece with a size of 79 mm × 972 mm was obtained.

[0076] <Preparation of electrolyte> In an argon atmosphere glove box with a water content of <10 ppm, a chain carbonate ester DEC and a cyclic carbonate ester EC were mixed in a mass ratio of 57.5:30 to obtain a base solvent, and a lithium salt LiPF6 was dissolved in the base solvent and mixed uniformly. Here, the mass fraction of LiPF6 was 12.5% ​​relative to the mass of the electrolyte, and the remainder was the base solvent.

[0077] <Preparation of separator> Water-based polyvinylidene fluoride, aluminum oxide, and polypropylene were mixed in a mass ratio of 1:8:1, added to deionized water, and stirred to obtain a coating layer slurry with a solid content of 50 wt%. The coating layer slurry was uniformly coated on one surface of a 5 μm-thick PE film (Celgard) and dried at 85°C to obtain a separator with a coating layer on one side and a coating layer thickness of 5 μm. The above steps were repeated on the other surface of the separator to obtain a separator with coating layers applied on both sides. Then, after drying and cold rolling, a separator was obtained. Here, the porosity of the separator was 39%.

[0078] <Preparation of lithium-ion batteries> The positive electrode pieces, separator, and negative electrode pieces prepared above were stacked in order and wound up so that the separator would be interposed between the positive and negative electrodes to play the role of isolation, and an electrode group was obtained. The electrode group was placed in an aluminum plastic film packaging bag, dried, and then poured with electrolyte, and the lithium ion battery was obtained through processes such as vacuum packaging, standing, formation (chemical formation), degassing, and cutting. Here, the formation conditions were to charge to 3.3V at a constant current of 0.02C, and then further charge to 3.6V at a constant current of 0.1C.

[0079] Examples 1-2 to 1-4 In Examples 1-2 to 1-4, the positive electrode active material R c / R i The average value of R and Dv50 of manganese dioxide are shown in Table 1. c3 / R i3 The results were the same as in Example 1-1, except that the average value of and Dv50 were adjusted.

[0080] Examples 1-5 and 1-6 In Examples 1-5 and 1-6, the raw material manganese dioxide was changed to trimanganese tetraoxide in the preparation of LMO, and the R of the positive electrode active material was c / R i The R of trimanganese tetraoxide was adjusted so that the average value of and Dv50 were as shown in Table 1. c4 / R i4 The results were the same as in Example 1-1, except that the average value of R and Dv50 were adjusted. c4 is the radius of the smallest circumscribing circle of the contour of the manganese oxide particle, and R i4 is the radius of the maximum inscribed circle of the contour of a manganese tetraoxide particle.

[0081] Example 2-1 In Example 2-1, in <Preparation of Positive Electrode Pieces>, the positive electrode active material LMO and the positive electrode active material LiNi 0.55 Co 0.15 Mn 0.3O2 (NCM5515), conductive agent SuperP, and binder polyvinylidene fluoride were mixed in a mass ratio of 76.8:19.2:2.4:1.6, and NMP was added and stirred with a vacuum mixer until homogeneous. A positive electrode slurry with a solid content of 75 wt% was obtained. The second particle R c / R i The average value of R of manganese dioxide and Dv50 of the positive electrode active material are shown in Table 2. c3 / R i3 The results were the same as in Example 1-1, except that the average value of and Dv50 were adjusted.

[0082] The above NCM5515 was obtained by the following method: Lithium carbonate (wherein the mass fraction of lithium element is 18.71%), and R c5 / R i5 The average value of Dv50 is 1.2 and Dv50 is 16.3μm. 0.55 Co 0.15 Mn 0.3 The (OH)2 precursor was mixed for 20 minutes at a rotation speed of 300 r / min in a high-speed mixer so that the ratio of the moles of Li to the moles of transition metal elements (the sum of the moles of Ni, Co, and Mn) was 1.05:0.997, and a mixture was obtained. The mixture was placed in an oxygen gas furnace, heated to 890°C at a rate of 5°C / min, maintained for 12 hours, and then taken out after natural cooling and sieved through a 300 mesh sieve to obtain lithium nickel cobalt manganese oxide, NCM5515. Here, R c5 Ni 0.55 Co 0.15 Mn 0.3 is the radius of the smallest circumscribing circle of the contour of the (OH)2 precursor particle, R i5 Ni 0.55 Co 0.15 Mn 0.3 is the radius of the maximum inscribed circle of the outline of the (OH)2 precursor particle.

[0083] Examples 2-2 to 2-4, and 2-7 In Examples 2-2 to 2-4 and 2-7, the corresponding positive electrode active materials were mixed according to Table 2, and R of manganese dioxide was added. c3 / R i3 Average value of Dv50 and / or Ni0.55 Co 0.15 Mn 0.3 (OH)2 Precursor R c5 / R i5 The average value of and Dv50 were adjusted, and the obtained R c1 / R i1 The average value of R c2 / R i2 The average value of the first particles, the area percentage of the second particles, the Dv50 of the positive electrode active material, and the particle size distribution (Dv90-Dv10) / Dv50 of the positive electrode active material are shown in Table 2, and the rest were the same as in Example 2-1. Here, NCM6010 in Table 2 is LiNi 0.6 Co 0.1 Mn 0.3 O2, and NCM8309 is LiNi 0.83 Co 0.09 Mn 0.08 The ratio of the mole number of Li to the mole number of transition metal elements in the preparation of NCM5515 was adjusted so that NCM6010 and NCM8309 satisfied the above chemical formula.

[0084] Examples 2-5 and 2-6 In Examples 2-5 and 2-6, in the preparation of the first particle LMO, the raw material manganese dioxide was changed to trimanganese tetraoxide, and the R of trimanganese tetraoxide was c4 / R i4 The average value and Dv50 of the manganese dioxide in the preparation of the second particle LMO were adjusted. c3 / R i3 The average value of and Dv50 were adjusted, and the obtained R c1 / R i1 The average value of R c2 / R i2 The average value of the first particles, the area percentage of the second particles, the Dv50 of the positive electrode active material, and the particle size distribution (Dv90-Dv10) / Dv50 of the positive electrode active material are shown in Table 2, and the rest were the same as in Example 2-1.

[0085] Examples 3-1 to 3-7 Examples 3-1 to 3-7 were similar to Example 2-1, except that the types and contents of the chain carbonate ester and cyclic carbonate ester were adjusted according to Table 3 to obtain the base solvent.

[0086] Examples 4-1 to 4-9 Examples 4-1 to 4-9 were similar to Example 2-1, except that in <Preparation of Electrolyte Solution>, a sulfonate ester compound was further added to the electrolyte solution, and the type and mass fraction of the sulfonate ester compound were adjusted according to Table 4.

[0087] Examples 5-1 to 5-6 Examples 5-1 to 5-6 were similar to Example 2-1, except that during the preparation process of LMO, an M2 metal element-containing compound was added according to Table 5, and the content was adjusted so that the mass fraction of metal element M2 was the value shown in Table 5.

[0088] Examples 5-7 Example 5-7 was similar to Example 5-3, except that commercially available LiFePO4 (denoted as LFP) with a Dv50 of 1.0 μm was used instead of NCM5515.

[0089] Examples 5-8 In Examples 5-8, instead of NCM5515, commercially available LiMn 0.75 Fe 0.25 The same as Example 5-3, except that PO4 (referred to as LMFP) was used.

[0090] Examples 5-9 Example 5-9 was the same as Example 5-3, except that a commercially available LFP having a Dv50 of 1.0 μm was used in place of a portion of the NCM5515, and the mass ratio of LMO, NCM5515, LFP, SuperP, and polyvinylidene fluoride was 76.8:9.2:10:2.4:1.6.

[0091] Comparative Example 1 Comparative Example 1 is R c / R iand the Dv50 of the positive electrode active material were as shown in Table 1, the same as in Example 1-1.

[0092] Tables 1 to 5 show the preparation parameters and performance measurements for each of the Examples and Comparative Examples.

[0093] [Table 1]

[0094] As can be seen from Examples 1-1 to 1-6 and Comparative Example 1, R c / R i When the value of is within the range of the present invention, the resulting lithium ion battery simultaneously has good low-temperature rate characteristics and room-temperature rate characteristics.

[0095] [Table 2]

[0096] The area percentage of the first particles, the area percentage of the second particles, the Dv50 of the positive electrode active material, and the value of (Dv90-Dv10) / Dv50 generally affect the performance of a lithium ion battery. As can be seen from Examples 2-1 to 2-7, when the area percentage of the first particles, the area percentage of the second particles, the Dv50 of the positive electrode active material, and the value of (Dv90-Dv10) / Dv50 are within the range of the present invention, the obtained lithium ion battery has good low-temperature rate characteristics and room-temperature rate characteristics.

[0097] [Table 3]

[0098] The type and mass fraction of the chain carbonate ester and cyclic carbonate ester in the electrolyte, as well as the value of ω1 / ω2, usually affect the performance of a lithium ion battery. As can be seen from Examples 2-1 and 3-1 to 3-7, when the type and mass fraction of the chain carbonate ester and cyclic carbonate ester, as well as the value of ω1 / ω2, are within the range of the present invention, the obtained lithium ion battery has good low-temperature rate characteristics.

[0099] [Table 4]

[0100] As can be seen from Example 2-1 and Example 4-1 to Example 4-9, adding a sulfonate ester compound to the electrolyte can improve the cycle characteristics of the lithium ion battery at high temperatures and the manganese elution phenomenon on the negative electrode piece. As can be seen from Example 4-1 to Example 4-9, when the type and mass fraction of the sulfonate ester compound are within the range of the present invention, the obtained lithium ion battery has good high-temperature cycle characteristics and the amount of manganese eluted on the negative electrode piece is small. In addition, when the value of A / B is within the range of the present invention, the obtained lithium ion battery has good high-temperature cycle characteristics and the amount of manganese eluted on the negative electrode piece is small.

[0101] [Table 5]

[0102] The type of element in the positive electrode active material usually affects the performance of the lithium ion battery. As can be seen from Example 2-1 and Example 5-1 to Example 5-9, when the positive electrode active material contains Mn and metal element M1, the obtained lithium ion battery has good low-temperature rate characteristics. In addition, when the second particles contain metal element M2 and the type and mass fraction of the metal element M2 are within the range of the present invention, the obtained lithium ion battery has good low-temperature rate characteristics.

[0103] The above are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the present invention.

Claims

1. 1. An electrochemical device comprising a positive electrode piece, the positive electrode piece comprising a positive electrode material layer, the positive electrode material layer comprising a positive electrode active material; In a scanning electron microscope photograph of a cross section of the positive electrode layer, an area of ​​5 μm 2 The radius of the minimum circumscribing circle of the contour of the positive electrode active material particle is R c and the area is 5 μm 2 The radius of the maximum inscribed circle of the contour of the positive electrode active material particle is R i Then, R c and R i is 1 < R c / R i The average value of ≦3 is satisfied, The electrochemical device further comprises an electrolyte; The electrolyte contains a chain carbonate ester and a cyclic carbonate ester, The mass fraction of the chain carbonate ester relative to the mass of the electrolyte is ω 1 and the mass fraction of the cyclic carbonate is ω 2 Then, ω 2 is 25% to 50%, and ω 1 / ω 2 is 0.75 to 2.

5.

2. The area is 5 μm 2 The positive electrode active material particles include a first particle and a second particle, The radius of the minimum circumscribing circle of the outline of the first particle is R c1 and the radius of the maximum inscribed circle of the contour of the first particle is R i1 Then, R c1 and R i1 is 1 < R c1 / R i1 The average value of ≦1.5 is satisfied, The radius of the minimum circumscribing circle of the contour of the second particle is R c2 The radius of the maximum inscribed circle of the contour of the second particle is R i2 Then, R c2 / R i2 is 1.5<R c2 / R i2 The electrochemical device according to claim 1 , wherein the average value of

3. With respect to a cross-sectional area of ​​the positive electrode material layer, an area percentage of the first particles is more than 0% and 50% or less, and an area percentage B of the second particles is 30% to 80%; the average cross-sectional area of ​​the first particles is smaller than the average cross-sectional area of ​​the second particles; The electrochemical device according to claim 2 , wherein at least one of the above is satisfied.

4. (a) the positive electrode active material contains lithium manganate; (b) the positive electrode active material includes a composite metal oxide of a lithium element and a transition metal element, the transition metal element includes Mn and a metal element M1, and the metal element M1 includes at least one of Ni, Co, and Fe; The electrochemical device according to claim 1 , which satisfies at least one of the following conditions:

5. The electrochemical device according to claim 2 , wherein the second particles include a metal element M2, and the metal element M2 includes at least one of Al, Mg, and Nb.

6. 3. The electrochemical device according to claim 2, wherein the second particles contain a metal element M2, and a mass fraction of the metal element M2 is 0.1% to 3% with respect to a mass of the second particles.

7. The volume particle size distribution of the positive electrode active material is (c) 9 μm≦Dv50≦22 μm; (d) 0.9≦(Dv90−Dv10) / Dv50≦2; and The electrochemical device according to claim 1 , which satisfies at least one of the following conditions:

8. 2. The electrochemical device according to claim 1, wherein the chain carbonate ester includes at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethyl propyl carbonate, dipropyl carbonate, methyl isopropyl carbonate, methyl butyl carbonate, and dibutyl carbonate.

9. 2. The electrochemical device of claim 1, wherein the cyclic carbonate comprises at least one of ethylene carbonate, propylene carbonate, and butylene carbonate.

10. 4. The electrochemical device according to claim 3, wherein the electrolytic solution contains a sulfonate ester compound, and when a mass fraction of the sulfonate ester compound with respect to a mass of the electrolytic solution is defined as A, A and B satisfy 0.006≦A / B≦0.

1.

11. The electrochemical device according to claim 10, wherein 0.5%≦A≦10% is satisfied.

12. The sulfonate ester compound is 【Chemistry 1】 The electrochemical device of claim 10 , comprising at least one of:

13. Further comprising a negative electrode piece, 2. The electrochemical device of claim 1, wherein the negative electrode piece includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of artificial graphite, natural graphite, and hard carbon.

14. An electronic device comprising an electrochemical device according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Positive electrode active material for lithium ion battery, positive electrode for lithium ion battery, and lithium ion battery

    JP2015056384A

  • Secondary battery, electrolyte, and device including secondary battery

    JP2022545896A